Pengaruh Perencanaan Pajak, Kebijakan Utang dan Struktur Modal Terhadap Nilai Perusahaan - Avita Kirani Putri; Dinar Ambarita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to analyse the effect of tax planning, debt policy and capital structure on firm value. The population used in this study are non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) with a period of 2019-2023. The research method used, namely quantitative research methods with panel data regression techniques and the type of data used in this study is secondary data, which is obtained indirectly by collecting financial reports and annual reports from Consumer Non-Cyclicals companies in 2019-2023 published on the IDX website or the official website of each company. This research is based on signal theory. The data collection technique used is the documentation method and literature study. The sample determination method uses purposive sampling method, with several predetermined criteria, there are 21 company samples from 125 company populations, and the observation results include 105 research data for five years in the 2019-2023 period. The independent variables used in this study, namely Tax Planning (X1), Debt Policy (X2) and Capital Structure (X3), and the dependent variable, namely Firm Value (Y). The data analysis method uses panel data regression analysis and hypothesis testing with a significant level of 5%. The results showed that the best model was the Fixed Effect Model (FEM). Based on the results of this study, simultaneously Tax Planning, Debt Policy, and Capital Structure affect Firm Value. Then, partially the results of this study indicate that Tax Planning and Capital Structure affect Firm Value, while Debt Policy has no effect on Firm Value.